Soybean performance under moisture limitation in a temperate tree-based intercropping system. (August 2022) - Gagné, Geneviève; Lorenzetti, François; Cogliastro, Alain; Rivest, David
Abstract: CONTEXT: Tree-based intercropping (TBI) systems show promise in reducing the vulnerability of field crops to increasing water stress. TBI can generate several above- and belowground interactions between trees and crops. These interactions remain poorly documented, especially in the context of moisture limitation. OBJECTIVE: The objective of this study was to determine the performance of soybean within a TBI system under moisture limitation. We hypothesized that TBI generates both positive (near the alleyway centre) and negative (near the trees) effects on soybean performance and that these effects are accentuated when moisture availability decreases. METHODS: A partial rainfall interception treatment (50% of the soil surface) in a soybean crop (stages R1 to R7) was installed for two years (2018 and 2019) in a TBI (50 trees/ha planted in 2012) in southern Quebec. TBI was composed of hybrid poplars (Populus deltoides × P. nigra) and different high-value hardwood species that were planted alternately within rows. A tree root-pruning treatment was also applied to understand belowground effects of tree roots on soybean growth under moisture limitation. Various microclimatic (light availability, wind speed and soil moisture) and soybean performance variables (leaf traits, 100-grain weight and yield) were measured at four distances from the tree row (4, 12 and 20 m, and control). RESULTS AND CONCLUSIONS: Rainfall exclusion decreased soil moisture and had a negative effect on soybean yield (−14%). The effect of the rain exclusion treatment on soybean performance was similar across all tree row distances and in both root-pruning treatments, which is contrary to our prediction. In 2018, an abnormally dry and warm season, yield near the alley centres was higher than near the tree row and tended to outperform the control. In 2019, a season with normal rainfall and temperature, soybean yield within the alleys was consistent among the different measured distances and did not differ from that in the control. Moderate shading at 4 m (−26% of PAR) was not associated with a change in soybean yield or leaf traits compared to other distances where shading was negligible or absent. Root pruning negatively affected soybean yield in 2018 (−14%) and 2019 (−22%), which is contrary to our prediction. SIGNIFICANCE: This case study adds to our knowledge regarding interactions between crops and trees in widely spaced TBI systems. TBI effects on spatial patterns of crop yield may vary substantially depending upon inter-annual variation in climatic conditions. This study suggests that more facilitative effects would prevail in dryer and warmer years, in contrast to near neutral effects in normal years. Graphical abstract: Unlabelled Image Highlights: Climate anomalies inciting water stress have become an important determinant of field crop yields Soybean performance was assessed within a TBI system under moisture limitation More facilitative effects of TBI system prevailed in the dryer year, while neutral effects occurred in the normal year Partial rainfall exclusion and tree root pruning had negative effects on soybean performance TBI systems may be viewed as an effective means of adaptation to climate change